Neutrophil-mediated anticancer drug delivery for suppression of postoperative malignant glioma recurrence - Xue, Jingwei; Zhao, Zekai; Zhang, Lei; Xue, Lingjing; Shen, Shiyang; Wen, Yajing; Wei, Zhuoyuan; Wang, Lu; Kong, Lingyi; Sun, Hongbin; Ping, Qineng; Mo, Ran; et al. (Nature nanotechnology, 2017)
Cell-mediated drug-delivery systems have received considerable attention for their enhanced therapeutic specificity and efficacy in cancer treatment. Neutrophils (NEs), the most abundant type of immune cells, are known to penetrate inflamed brain tumours. Here we show that NEs carrying liposomes that contain paclitaxel (PTX) can penetrate the brain and suppress the recurrence of glioma in mice whose tumour has been resected surgically. Inflammatory factors released after tumour resection guide the movement of the NEs into the inflamed brain. The highly concentrated inflammatory signals in the brain trigger the release of liposomal PTX from the NEs, which allows delivery of PTX into the remaining invading tumour cells. We show that this NE-mediated delivery of drugs efficiently slows the recurrent growth of tumours, with significantly improved survival rates, but does not completely inhibit the regrowth of tumours. Neutrophils carrying drug-containing liposomes can suppress recurrence of brain tumours after surgical removal of the tumour.